Combatting Cyberbullying and Promoting Adolescent Mental Health: A Focus on Evidence Based Interventions - Afrianto , Indra (Journal of Health Literacy and Qualitative Research, 2023)
Cyberbullying has become a critical issue affecting children and adolescents, with increasing evidence linking it to severe mental health consequences. This study aims to examine the prevalence, psychological impact, and potential interventions to mitigate cyberbullying’s harmful effects. A systematic review methodology was employed, analyzing peer-reviewed studies from databases such as PubMed, Scopus, and PsycINFO. The findings reveal that cyberbullying significantly contributes to depression, anxiety, self-esteem issues, and suicidal ideation among victims. The role of protective factors, such as parental support and school-based interventions, is highlighted as crucial in minimizing these risks. Additionally, the study explores the dual role of technology and social media algorithms in either exacerbating or mitigating cyberbullying incidents. While platforms enable online harassment, technological interventions, including content moderation and reporting tools, present potential solutions. Given the growing prevalence of cyberbullying, urgent action is needed. Schools should implement digital literacy programs, while policymakers must enforce stricter regulations on social media content. Future research should focus on assessing intervention effectiveness, exploring cross-cultural differences, and leveraging AI for cyberbullying detection. Addressing cyberbullying requires a multi-disciplinary approach, integrating education, technology, and policy to safeguard children's mental health in digital spaces.